BIOACESSIBILIDADE DE ELEMENTOS METÁLICOS E COMPOSTOS FENÓLICOS EM CHÁS DE Miconia albicans E DE Senna alexandrina - BUTIK, MARIANE (2023)
Many medicinal plants are popularly used for their health benefits. Its use is mainly due to the consumption of teas, where the compounds present in plants are extracted, benefiting those who consume it. Among the various species of plants used for this purpose, Canela de Velho (CV) (Miconia albicans) stands out. Also noteworthy is Senna (Senna alexandrina) used as a tea to treat constipation and even for weight loss. However, works on the chemical composition of these plant species are scarce in the literature. Thus, this work sought to determine the concentrations of Al, Ca, Cr, Cu, Mg and Zn in these plants, as well as the bioaccessible fractions of these metallic elements, using in vitro assays, simulating gastrointestinal digestion processes after validation in house - using gastric and intestinal juices. For this purpose, 10 samples of CV and 9 samples of Sene were acquired in Guarapuava-PR. The contents of inorganic nutrients were determined by atomic absorption spectrometry (AAS). Total phenolic and flavonoid contents and bioaccessible fractions were also determined in these samples using UV-vis spectrometry. For all CV samples, total and bioaccessible concentrations were found for metallic elements Al, Ca, Cu and Mg. And for organic compounds all samples showed bioaccessible concentrations and fractions, and for total flavonoids the bioaccessible fractions were on average 55% and for total phenolics 84%. For all Sene samples, total and bioaccessible concentrations of the metallic elements Ca, Cu and Mg were quantified, and in only one sample the concentration and bioaccessibility of Zn was not determined, and Al was not detected in any sample. And for organic compounds all samples showed concentrations and bioaccessible fractions, and for total flavonoids and total phenolics the bioaccessible fractions were around 88%. In the principal component analysis (PCA) between metals and organic compounds in CV samples, it was observed that for some samples, the smaller the bioaccessible fraction of organic compounds, the greater the fraction of metals. The ACP for the Sene samples shows correlation of organic compounds, Cu and Mg for some samples, which are inversely proportional with the samples that presented higher bioaccessible fractions of Ca and Zn metals. Consumption of CV and Senna teas does not exceed the RDI of the studied metals.